Professional Online Presence and Learning Networks: Educating for Ethical Use of Social Media - Forbes, Dianne (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
In a teacher education context, this study considers the use of social media for building a professional online presence and learning network. This article provides an overview of uses of social media in teacher education, presents a case study of key processes in relation to professional online presence and learning networks, and highlights issues and challenges for wider consideration. Specific practical illustrations are provided, relating experiences when starting out with social media, integrating coursework challenges for student teachers, and considering feedback and future planning. Social media is used in teacher education for sharing content, discussing, and collaborating. There are challenges and risks with social media in an academic context. Students require differentiated scaffolding depending on their expertise and confidence. In terms of social implications, professionals are warned to safeguard online reputation, while making proactive use of social media to enhance learning networks.